GrAHal-CAPP for axion dark matter search with unprecedented sensitivity in the 1–3 μeV mass range - Pugnat, Pierre; Camus, Philippe; Kwon, Ohjoon; Ballou, Rafik; Bruyère, Cyril; Byun, Heesu; Chung, Woohyun; Grenet, Thierry; Perrier, Pierre; Semertzidis, Yannis K.; Talarmin, Arthur; Vessaire, Jérémy (Frontiers in Physics, 2024)
A collaboration between CNRS-Grenoble and IBS-CAPP Daejeon plans to build a Sikivie's type haloscope for axion/ALPs dark matter search at the Dine-Fischler-Srednicki-Zhitnitskii (DFSZ) sensitivity for the 300-600 MHz range. It will be based on the large bore superconducting "outsert" coil of the Grenoble hybrid magnet providing a central magnetic field up to 9 T in 810 mm warm bore diameter. This magnet has just been successfully powered up to 8.5 T achieving the first step of the electrical commissioning phase. The design principles of the cryostat with its double dilution refrigerators to cooldown below 50 mK, the light Cu RF-cavity of 700 mm diameter together with its tuning rod(s) and first stages of the measurement chain, are presented. Perspectives for the targeted sensitivity assuming less than 2-year integration time is given.